P–081 Microfluidic sorting does not improve clinical outcomes compared to magnetic activated cell sorting (MACS) in Assisted Reproduction. (6th August 2021) - González-Ravina, C; Pachec. Castro, A; Cru. Palomino, M; Requen. Miranda, A
Abstract: Study question: Does microfluidic sorting improve clinical outcomes over magnetic activated cell sorting (MACS) in ovum donation cycles? Summary answer: Performing microfluidic sorting does not seem to improve clinical outcomes compared to MACS in ovum donation cycles. What is known already: Novel sperm selection techniques, such as magnetic activated cell sorting (MACS), have been described as useful procedures to increase reproductive outcomes when male factor is present. Because of centrifugation steps associated to swim-up or density-gradient can induce sperm DNA fragmentation, microfluidic sperm sorters are being used to isolate motile human spermatozoa based on fluid dynamics and avoiding sample manipulation. This new technology has been shown to reduce the level of sperm DNA damage, especially double strand breaks, but an improvement of clinical outcome by using this technique remain unclear. Study design, size, duration: Prospective and observational study to evaluate the efficacy of a sperm sorting technique based on microfluidic technology versus a technique based on the removal of apoptotic spermatozoa by MACS. The study was performed between May 2019 to January 2021 in IVI Madrid and IVI Sevilla. All men attending for an ovum donation cycle during the aforementioned study period were included. The exclusion criteria were sperm concentration <5 mill/mL and <15% of progressive motile spermatozoa. Participants/materials, setting, methods: Seminal samples from couples participating in the study were divided into two aliquots; each of them was processed according to one of the study methods. Subsequently, each of the processed sperm samples was used to microinject half of the oocytes obtained during oocyte retrieval. In all case, a single-embryo transfer was performed. Variables were expressed as mean values and standard deviations. Statistical analysis was performed by ANOVA and Chi-squared where applicable; significance established under 0.05. Main results and the role of chance: We included 48 couples in the study; of these, n = 31 transferred an embryo derived from a MACS processed sperm sample, while n = 17 received an embryo from the microfluidic one. Groups were homogeneous in terms of number of transferred embryos and frozen embryos, usable blastocyst rate and fertilization rate; results were as follows for MACS and microfluidic processing respectively: number of transferred embryos (1.0±0.0 vs. 1.0±0.0, p = 0.978); number of frozen embryos (1.6±0.5 vs. 1.4±0.7 p = 0.168); usable blastocyst rate (40.7% vs. 43.1%, p = 0.384); and fertilization rate (80.4% vs. 75.3%, p = 0.075). However, according clinical outcomes, we observed significant differences in implantation rate (74.2% vs. 58.8%, p < 0.001) and in clinical pregnancy rate (74.2% vs. 58.8%, p < 0.001); finally, the miscarriage rate was similar between the two groups of study (6.4% vs. 5.8%, p = 0.876). Limitations, reasons for caution: This study has not considered the indication in male factor couples due to a high degree of double-strand DNA fragmentation. Therefore, more specific studies are required to determine in which patients, microfluidics sorter selection would significantly improve clinical outcomes. Wider implications of the findings: In an unselected population, magnetic activated cell sorting significantly improves clinical outcomes compared to a microfluidic technique, so this latter method should not be recommended without a male factor indication associated with sperm DNA damage. The proposed microfluidic technology does not seem to offer a flow-free approach to select spermatozoa. Trial registration number: NCT04061486